Reversal strategy in antagonizing the P2Y12‐inhibitor ticagrelor. (23rd September 2013) - Hobl, Eva‐Luise; Derhaschnig, Ulla; Firbas, Christa; Schoergenhofer, Christian; Schwameis, Michael; Jilma, Bernd
Abstract Background Patients on antiplatelet therapy have a higher incidence of bleeding complications. Reversal of antiplatelet drug effects is an important issue at trauma or emergency departments. For old and conventional anticoagulants, reversal strategies are established. While the effects of ticagrelor are reversible, developing a method to restore platelet function in patients is of importance due to its longer half‐life (approximately 8 h), compared with other P2Y12‐inhibitors. Materials and methods We report an ex vivo model to reverse the effects of the novel and highly effective P2Y12‐inhibitor ticagrelor in 20 healthy volunteers. To normalize platelet reactivity, we added increasing amounts of autologous platelet‐rich plasma (PRP) to whole blood which was obtained 3 h after the intake of 180 mg of ticagrelor. Platelet aggregation was assessed by whole blood multiple electrode aggregometry (MEA), which is based on impedance aggregometry. Results The basal ADP‐induced platelet aggregation averaged 71 ± 16 U (Units). Ticagrelor decreased ADP‐induced platelet aggregation to 16 ± 8 U. A clear dose‐response was obtained after spiking whole blood with increasing amounts of PRP. It is estimated that ≥2 units of apheresis platelet concentrates will be necessary to completely restore baseline platelet aggregation in the majority of patients after ticagrelor. Conclusions Platelets dose dependently improve ex vivo platelet aggregation of subjects after a loading dose of 180 mg of ticagrelor, making transfusion of platelet concentrates potentially useful in bleeding patients and those who need to undergo emergency surgery.